1985
DOI: 10.1093/nar/13.7.2559
|View full text |Cite
|
Sign up to set email alerts
|

α-Putrescinylthymine and the sensitivity of bacteriophageφW-14 DNA to restriction endonucleases

Abstract: The modified base alpha-putrescinylthymine (putT) in phi W-14 DNA blocks cleavage of the DNA by 17 of 32 Type II restriction endonucleases. The enzymes cleaving the DNA do so to widely varying extents. The frequencies of cleavage of three altered forms of the DNA show that putT blocks recognition sites either when it occurs within the site or when it is in a sequence flanking the site. The blocking is dependent on both charge and steric factors. The charge effects can be greater than the steric effects for som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Also structural modifications have a strong impact on the stability of such duplexes. Therefore, in a first series of experiments, 7-deazaadenine residues carrying alkynyl groups different in length or size of the alkynyl chain were used to replace the adenine base of 5'-d(A-T) 6 (8). The T m values and thermodynamic data of the various oligonucleotide duplexes were determined for buffer solutions containing Mg 2 ions and 1.0m or 0.1m NaCl (see Table 3).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Also structural modifications have a strong impact on the stability of such duplexes. Therefore, in a first series of experiments, 7-deazaadenine residues carrying alkynyl groups different in length or size of the alkynyl chain were used to replace the adenine base of 5'-d(A-T) 6 (8). The T m values and thermodynamic data of the various oligonucleotide duplexes were determined for buffer solutions containing Mg 2 ions and 1.0m or 0.1m NaCl (see Table 3).…”
Section: Methodsmentioning
confidence: 99%
“…The bulky estradiol-modified ethynyl residue (see 1i) resulted in significant duplex destabilization when only one modified base was incorporated ( Table 3). For selfcomplementary oligonucleotide duplexes containing a modified dA 6 tract, enhanced duplex stability was observed when a 7-deaza-7-ethynyladenine was introduced (see 5'- Table 3, it can be concluded that alkynyl side chains up to a length of 6 ± 7 , which is about the depth of a B-DNA major groove (8.8 ; [33]), lead to duplex stabilization, while longer residues destabilize the duplex structure.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations